The Development Model for Customer Relationship Management (CRM) to Improve The Quality of Services in Academic Information Systems Faculty of Computer Science Sriwijaya University - Fathoni Fathoni (ICON-CSE, 2014)
The development and utilization of information technology will make the competition among universities, as a result the universities should maintain their quality of services to get their potential customers and key customers, in particularly to get related information, in order to being first choice in the society. Professional management will be able to provide outstanding quality services and highly competitive, especially in academic services. The development of academic information system to improve the services can be done by apply the Customer Relationship Management or (CRM). Implementation of CRM in academic information system can create an emotional bond that is able to build a two-way communication between users and academic system providers. With good and reliable communication can improve the quality of academic services to the customers, which in turn will be able to improve the customer loyalty and increase the customer satisfaction in the Faculty of Computer Science.